Tindak Tutur Ilokusi Komisif Sajrone Film Jayadi 2020 Anggitane Hajar Pamuji (Tintingan Pragmatik) - Alfionita Herminda; Udjang Pairin (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Commissive illocutionary speech acts are a type of speech act that speakers understand to bind themselves to take action in the future. Commissive illocutionary speech acts aim to provide information to their speech partners. The research method used in this study uses a qualitative descriptive method. This method is used to examine natural objects and also describe an image or video systematically. In this study, the researcher conducted a film study taken from YouTube, entitled